2014
DOI: 10.3109/08820538.2014.962155
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens Care among Teenage Students in Italy: A Cross-Sectional Study

Abstract: Many students don't properly care for their CL. Education regarding proper care and management of CL among users is advised in view of frequency of symptoms and complications reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 17 publications
6
17
2
Order By: Relevance
“…To our knowledge, this study is the first to collect a dataset on the prevalence of CL wear amongst teenagers in rural areas in Malaysia. The percentage obtained was lower than the reported prevalence of CL wear amongst teenagers living in urban areas, such as Kuala Lumpur (9.9%) [18] and Rome (9.4%) [19]; such percentage was probably due to the lower prevalence of refractive error and smaller family income. A report from the Department of Statistics, Malaysia (2013) has shown that the average income of families residing in rural areas is lower than the income of those in Kuala Lumpur.…”
Section: Discussioncontrasting
confidence: 71%
“…To our knowledge, this study is the first to collect a dataset on the prevalence of CL wear amongst teenagers in rural areas in Malaysia. The percentage obtained was lower than the reported prevalence of CL wear amongst teenagers living in urban areas, such as Kuala Lumpur (9.9%) [18] and Rome (9.4%) [19]; such percentage was probably due to the lower prevalence of refractive error and smaller family income. A report from the Department of Statistics, Malaysia (2013) has shown that the average income of families residing in rural areas is lower than the income of those in Kuala Lumpur.…”
Section: Discussioncontrasting
confidence: 71%
“…This group of patients who presented to healthcare institutions with cosmetic contact lens-related complications were also less likely to adhere to scheduled follow-up consultations compared to counterparts wearing conventional contact lenses [62]. The findings by Abbouda et al, mirror findings of the Contact Lens Assessment in Youth (CLAY) study, which has demonstrated the greatest risk of developing corneal infiltrates in patients was between the age of 15-25 [65,66]. It was further found that patients younger than 15 years of age were more compliant with recommended lens wear habits [66].…”
Section: Patient-related Factorsmentioning
confidence: 78%
“…Non-compliance with recommended lens wear habits Patients are less likely to adhere to recommended safe lens wear practices and scheduled follow-up consultations [3,44,62,65].…”
Section: Cosmetic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young contact lens wearers are usually unaware of the risks to which they are exposed. 34 Therefore, health education regarding CCL use for the teenage and young adult population, together with the role of optometrists or ophthalmologists as guides, should be emphasized.…”
Section: Discussionmentioning
confidence: 99%